Borderline personality: revisiting its classification as a neurodevelopmental disorder - Laurini, Olivier; Strugarek, Perrine; Rahioui, Hassan (Frontiers in Psychiatry, 2025)
Although borderline personality disorder is classified as a personality disorder, many studies have developed arguments in favor of a neurodevelopmental origin. In order to methodologically advance this new conceptualization of the disorder, we have identified six criteria for inclusion in the diagnostic category of neurodevelopmental disorders and propose to examine the extent to which borderline disorder may meet these criteria, illustrating them with recent studies.Our review allows us to put forward the idea that this pathology could be considered as a late-onset neurodevelopmental disorder, present in childhood but fully manifesting in adolescence, a critical and rather explosive period of the developing brain. Such a perspective could help with early detection and treatment.